If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y = 2y + 9 + 7y Reorder the terms: 10y = 9 + 2y + 7y Combine like terms: 2y + 7y = 9y 10y = 9 + 9y Solving 10y = 9 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. 10y + -9y = 9 + 9y + -9y Combine like terms: 10y + -9y = 1y 1y = 9 + 9y + -9y Combine like terms: 9y + -9y = 0 1y = 9 + 0 1y = 9 Divide each side by '1'. y = 9 Simplifying y = 9
| 5(x+2)=3x+22 | | 28x^3+59x^2+13x= | | 14x(x-2)(x+4)=0 | | 5x+6=81 | | 12+x=5+8x | | 3x^2+11x-15=0 | | 2x+3=12-8x | | 3y+4=x+13 | | 2x+10=12-7x | | c=222r | | 2x^2+20x+42=0 | | 2x+10=12-2x | | n^2+n=72 | | 5y-7=15 | | h+2=8 | | 3x+8=9-7x | | 6x-5y=18 | | (x+16)(x-4)=0 | | 13x+2=9-7x | | h+7=16 | | 13x+2=9-8x | | 16+3x=94 | | 3y^2-y-14=0 | | 4y+5=2x | | 4x^2-29x+30=0 | | 3-x=2y | | -36+5y=-7y | | 24+12x=9-3x | | a+5=10 | | 4q=12 | | 3x+7y=2 | | 32t+20=116 |